Analysis of Virome by High-Throughput Sequencing Revealed Multiple Infection and Intra-Virus Diversity in a Single Grapevine Plant - Glasa, Miroslav; Predajna, Lukas; Sihelská, Nina; Soltys, Katarína; Ruiz-García, Ana B. (Faculty of Horticulture and Landscape Engineering/Slovak University of Agriculture in Nitra., 2021)
The ribosomal-depleted total RNA from white-berry grapevine (Vitis vinifera, SK933) plant showing severe chlorosis and downrolling of leaves was used for the high-throughput sequencing (HTS) analysis in order to unravel the potential contribution of the viral pathogens to the symptomatology observed. The combination of de novo assembly and mapping of ca. 1.1 millions of HTS reads enabled to identify and characterise a complex viral/viroid infection involving Grapevine leafroll-associated virus-2 (GLRaV-2), Grapevine leafroll-associated virus-3 (GLRaV-3), Grapevine rupestris stem pitting-associated virus (GRSPaV), Grapevine rupestris vein feathering virus (GRVFV), Grapevine Syrah virus-1 (GSyV-1) and Hop stunt viroid (HSVd). The determined nearly complete genomes of GLRaV-2 SK933 showed its high genetic divergence from previously characterised isolates. In case of GRSPaV, two variants representing different evolutionary lineages have been identified in the plant. The results further pinpoint the complexity of grapevine viral diseases and show that mixed virus infection of grapevine is rather a rule than an exception.